Development of Culinary Business Slepiban (Banana Rolls) to Increase Interest in Entrepreneurship among Students - Adhartini, Mia Aidul; Amellisa , Julyananda; Rama, Dhini Wijayanti (CV Media Inti Teknologi, 2024)
Indonesia is the country that produces the most bananas. This is because Indonesia's climate is very suitable for the growth of banana plants. Banana is one of the most important horticultural crops in the world because of their large production potential. Bananas have long been known as a delicious and nutritious fruit for health, for example as a remedy for diarrhea. Banana rolls are an entrepreneurial product made as a healthy snack today. Selpiban (banana rolls) is a product made from processed bananas that are flattened and then rolled and topped with toppings. This product is made from bananas that are ripe enough to have a sweet taste. The purpose of making banana rolls is as a healthy snack or snack that has high nutritional value, and to use bananas as a food ingredient which is quite popular among all ages, from children to the elderly. In its market segmentation , it targets all groups, from children, and teenagers, to adults, even the elderly. This food product is safe for consumption by all groups because it does not cause side effects. In addition, this rolled banana product from Slepiban has many benefits because it is made from premium ingredients that are rich in nutrients. However, more specifically, the slepiban market segmentation tends to be for children teenagers, and housewives. The reason is that this group prefers snack products such as banana rolls. Due to these considerations, this rolled banana product from slepiban will sell well among children and adolescents as well as housewives.